Acceptability of Telepsychiatry in American Indians - Shore, Jay H. (Mary Ann Liebert, Inc., 2008)
Telepsychiatry differs from in-person treatment in terms of its delivery mechanism, and this dissimilarity may increase cultural differences between the provider and the patient. Because cultural competence and identification can impact patient satisfaction ratings, we wanted to explore whether cultural differences in our study population influenced telepsychiatric and in-person interviews. Here, we compared the acceptability of conducting psychiatric assessments with rural American Indian veterans by real-time videoconferencing versus in-person administration. The Structured Clinical Interview for DSM-IIIR (SCID) was given to participants both in person and by telehealth. A process measure was created to assess participants' responses to the interview type concerning the usability of the technology, the perceptions of the interviewee/interviewer interaction, the cultural competence of the interview, and satisfaction with the interview and the interview process. The process measure was administered to 53 American Indian Vietnam veterans both in-person and by real-time interactive videoconferencing. Mean responses were compared for each participant. Interviewers were also asked several of the same questions as the participants; answers were compared to the corresponding participant responses. Overall, telepsychiatry was well received and comparable in level of patient comfort, satisfaction, and cultural acceptance to in-person interviews. We also found evidence to suggest that interviewers sometimes interpreted participant satisfaction as significantly less favorable than the participants actually responded. Despite the potential of videoconferencing to increase cultural differences, we found that it is an acceptable means for psychiatric assessment of American Indian veterans and presents an opportunity to provide mental health services to a population that might otherwise not have access.